“The fight of our generation”: Metaphors, code switching, and ideological constructions in announcement speeches of presidential aspirants - Rodriguez, Maxine Rafaella G (Diliman Review; Vol 66 No 1 (2022), 2024)
This study determines the rhetorical strategies of and analyzes the linguistic ideologies established by Ping Lacson, Bongbong Marcos, Isko Moreno, Manny Pacquiao, and Leni Robredo, presidential aspirants for the 2022 Philippine national elections, in speeches delivered during their respective official announcements of filing for candidacy. Conceptual metaphor theory, functions of code switching, and ideological discourse analysis were used to answer the following research questions: What are the discursive strategies commonly found in all of the candidates’ announcement speeches? How do these strategies construct the identities of the candidates in their announcement speeches? What are the socio-political implications of these strategies against the background of the national elections? The candidates were found to self-represent via Lacson is ideal leader, Marcos is unity, Moreno is cure, Pacquiao is messiah, and Robredo is fighter. In terms of code switching, the candidates can be positioned in a spectrum on whose one end would be Robredo appealing most to nationalistic sentiments with the majority of her speech in Filipino, and on the other would be Marcos appealing least with a majority of English words. Ideological discourse analysis yields an Us vs. Them dichotomy in which the electorate is targeted to be allied with the candidate, and the previous Duterte administration and the pandemic as misaligned and therefore othered. Results from this analysis contribute to the scholarship of presidential rhetoric in the Philippines, an understudied field of study, and help evaluate the winning candidate’s first year of the presidency summarized via the State of the Nation Address (SONA) last 24 July 2023.